Rwanda : Tenth Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This is the tenth and final review of Rwanda's PSI-program, approved by the Executive Board on December 2, 2013. A concurrent 18-month SCF arrangement was approved on June 8, 2016 to support adjustment policies to eliminate external imbalances. The PSI-supported program was extended three times, on: June 8, 2016; November 19, 2017; and January 12, 2018. When it expires on December 1, 2018, the program will have reached its maximum 5-year limit. Recent Developments. After a dip in 2016-17, real GDP growth has been recovering over the past four quarters. Growth averaged 8.6 percent in the first half of 2018 and, despite a temporary deceleration in Q2, remains in line with projections for 7.2 percent for the year. Growth in the medium term should remain at or higher than historical averages, based on a strong pipeline of tourism and business tourism, new mining operations, more resilient agriculture, new and more diversified exports, and construction of a new airport. Inflation remains low, and expectations within targeted ranges. External balances and reserve buffers continued to improve, while the financial sector remains healthy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet